500 paper objects : new directions in paper art - McHugh, Gene (Lark Crafts, 2013)
"Paper craft is a dynamic medium that's in the midst of a renaissance--and this entry in the very popular Showcase 500 series reveals the creative work of today's most gifted and original artists and the limitless potential of the craft. Juried by Gene McHugh, an award-winning arts writer and well-established expert in the field, the book presents a broad range of techniques, forms, and aesthetic approaches, with magnificent examples of origami, kirigami, cutting, quilling, papier-mâche;, and casting. "--